2016
DOI: 10.1186/s13063-016-1189-4
|View full text |Cite
|
Sign up to set email alerts
|

From protocol to published report: a study of consistency in the reporting of academic drug trials

Abstract: BackgroundUnacknowledged inconsistencies in the reporting of clinical trials undermine the validity of the results of the trials. Little is known about inconsistency in the reporting of academic clinical drug trials. Therefore, we investigated the prevalence of consistency between protocols and published reports of academic clinical drug trials.MethodsA comparison was made between study protocols and their corresponding published reports. We assessed the overall consistency, which was defined as the absence of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 29 publications
1
12
0
Order By: Relevance
“…RCTs, respectively [10]. In the subgroup of the 126 academic trials in our cohort, discrepancies in primary endpoints were found in 10 of 54 RCTs (19%), and in 13 of 72 non-RCTs (18%).…”
Section: Discussionmentioning
confidence: 67%
See 3 more Smart Citations
“…RCTs, respectively [10]. In the subgroup of the 126 academic trials in our cohort, discrepancies in primary endpoints were found in 10 of 54 RCTs (19%), and in 13 of 72 non-RCTs (18%).…”
Section: Discussionmentioning
confidence: 67%
“…In addition to the sponsor type, we analyzed the trial characteristics that were significantly associated with nonpublication in the same cohort [21]: phase, centers involved, prospective registration, and completion. Furthermore, in line with previous studies [9,10], we also analyzed the association of the trial design and the treatment arms with discrepancies in the primary endpoints. The protocol of our study [7] prescribed the analysis of determinants for all protocol-publication discrepancies separately.…”
Section: Methodsmentioning
confidence: 95%
See 2 more Smart Citations
“…Unfortunately, discrepancies between a registered trial protocol and its publication are still frequently reported. [5][6][7][8] Since July 2005, the International Committee of Medical Journal Editors requires trials to be registered before the enrolment of the first patient in order to prevent selective publication of trial outcomes in an effort to reduce this form of publication bias. 9 Besides the obligation to publish trial results, it is essential that these results become available within an appropriate period to ensure that clinical decisions can be made on the most recently available evidence.…”
Section: Introductionmentioning
confidence: 99%